(untitled) (International Journal of Built Environment and Sustainability, 2025)
Facilities management (FM) is a discipline which supports an organization in efficient execution of its core business. Construction schemes are usually financially costly, with policymakers of both industrialized and emerging countries implementing Public Private Partnership (PPP) to finance public sector projects for pragmatic purposes. the research aims to review the conceptual framework of Public Private Partnership in Facility Management. For this research, secondary source of data was employed as methods of data collection, different relative articles and journals were review, where qualitative method was used in data analysis. The study reviewed that the key to FM PPP considerations that government and private sector should concentrate on: Strengthening the framework of the PPP policy, Legal and regulatory structure alignment and Guidelines for applying PPP and system procedures. PPP procurement comprises 4 stages that include Public Authority is accountable for the first stage of the PPP programme. The second step of the PPP process deals with project appraisal. The third section of the PPP process includes the marketing and bidding process of the project. Negotiations are the next step of the PPP process,Therefore, there is need for federal government, state government and local government in Nigeria to adopt it which will assist in improving the quality, life span of the public facilities properties, as most of the conditions of these properties are in stage of dilapidated, old stage or are about to be affected by obsolescence.